Effects of the entrepreneurial strategic orientation of social enterprises on organizational effectiveness: Case of South Korea - Changwon Cho; Bo-Young Kim; Sung Ho Oh (Administrative Sciences, 2022)
This study aims to empirically verify whether the entrepreneurial strategic orientation of social enterprises has any effect on organizational effectiveness with the mediation of dynamic capabilities. In the consideration of social enterprises' features, strategic orientation consisted of social value orientation, entrepreneurial orientation, and market orientation. Dynamic capabilities consisted of absorption capacity and coordination capacity, and organizational effectiveness was comprised of job satisfaction and organizational commitment. An online questionnaire survey targeted 228 employees of Korean social enterprises. The survey results were analyzed using a structural equation. As a result of the analysis, entrepreneurial orientation and market orientation significantly affected absorption capacity, but social value orientation did not affect it. Social value orientation and market orientation significantly affected coordination capacity, but entrepreneurial orientation did not affect it. Absorptive capacity and coordination capacity affected organizational effectiveness, and the hypotheses were adopted. Consequently, it was revealed that market orientation had the most significant effects on social enterprises' dynamic capabilities and organizational effectiveness. It was confirmed that social value orientation and entrepreneurial orientation revealed differences depending on the absorptive capacity and coordination capacity of dynamic capabilities.
Keywords: 350; absorptive capacity; coordination capacity; dynamic capabilities; organizational effect; social enterprise; strategic orientation